Pastizales naturales. Guía de condición - Kropfl, Alicia; Giorgetti, Hugo; Alvarez, Juan Mauricio; Villasusso, Natalia; Pelotto, Pablo; Kugler, Nora Maria (EEA Valle Inferior, INTA, 2022)
EEA Valle Inferior